“Restoring the Soul of Business: Staying Human in the Age of Data” - Tobaccowala , Rishad; Dewan , Rakhee (Gyan Management Journal, 2020)
This book propounds that the key to successful change in any association lies between human instinct and information-driven bits of knowledge. The author portrays that how computerized apparatuses and humans coordinated expertly in digilog organizations to build up a cognizance and figure out how to be proactive when they see cautioning signs that human characteristics are being subjected to innovation and information just choices. The book highlights procedures and tools which any association or company can adopt. It also provokes readers to push ahead with the sort of equalization that catalyzes change and delivers one incredible accomplishment after another. The book is divided into three sections and twelve chapters. Section I includes three chapters and it focused on the challenges: carbon-based, analog feeling human in silicon infused digital and data-driven world. It guides how an employee can prompt expanded income, retention, productivity, and even bliss in their jobs and business with the best possible harmony between human instinct, imagination, and data-driven bits of knowledge. The author underlined that how employees and companies can release huge advantage by consolidating feeling and information, human and machine, simple and advanced. Even emphasized on the admonition indications of the companies which are data-focused such as helpless client assistance because of computerized, automated procedures that cause dissatisfaction towards a brand, less employee involvement in decision making, and helpless development coming from smothered workers not urged to contribute thoughts or experiences.